2020
DOI: 10.1016/j.chc.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Childhood-onset Schizophrenia 2019 Update

Abstract: they relate to the genetic architecture of schizophrenia. The authors subsequently provide an overview of major genetic findings for AOS, including reviewing studies of common, rare, and copy number variants in AOS. Finally, the authors will review genetic studies of COS, more specifically. Of note, many modern, large-scale genome-wide association studies of schizophrenia involve minimal patient characterization aside from establishing schizophrenia case status. As such, age of onset is often not reported. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 77 publications
0
17
0
1
Order By: Relevance
“…It is generally believed schizophrenia is caused by environmental and genetic factors and genetic factors play an important role (Fan et al, 2018; Forsyth & Asarnow, 2020; Fusar‐Poli et al, 2014; Murray et al, 2017). This study showed that 23.7% of EOS patients had a positive psychiatric family history, similar to the results of previous studies (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed schizophrenia is caused by environmental and genetic factors and genetic factors play an important role (Fan et al, 2018; Forsyth & Asarnow, 2020; Fusar‐Poli et al, 2014; Murray et al, 2017). This study showed that 23.7% of EOS patients had a positive psychiatric family history, similar to the results of previous studies (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently in 2017 Chaumette and colleagues identified three de novo pathogenic variants in the ATP1A3 gene (p. Asp801Asn; p.Glu815Lys; p. Ala813Val) in three unrelated individuals with COS, two of them also had AHC. One also had characteristics of autistic spectrum disorder (ASD) ( 61 ), which is frequently seen in COS ( 62 ).…”
Section: Reviewmentioning
confidence: 99%
“…The diagnosis of EOS is based on the same criteria as in patients diagnosed with Adult Onset Schizophrenia (AOS), with a good long-term diagnostic stability (Maziade et al, 1996). Before the introduction of DSM-III, the diagnostic criteria for EOS were not well established (Forsyth and Asarnow, 2020). In addition, the occurrence of EOS is usually preceded by a period of normal development.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-Wide Association Studies (GWAS) of AOS patients involving more than 16,161 individuals did not indicate significant changes. For this reason and due to the low prevalence of EOS, GWAS on EOS patients have not yet been performed (Forsyth and Asarnow, 2020). Importantly, only in one third of genetic studies related to EOS, the full phenotype of patients is described (Fernandez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%